CDK9 Regulates Apoptosis of Myoblast Cells by Modulation of microRNA‐1 Expression. Issue 1 (11th July 2017) - Tarhriz, Vahideh; Wagner, Kay‐Dietrich; Masoumi, Zahra; Molavi, Ommoleila; Hejazi, Mohammad Saeid; Ghanbarian, Hossein
ABSTRACT: Cdk9 is the catalytic core of the positive transcription elongation factor b (P‐TEFb) and regulates transcriptional elongation factors by phosphorylation of RNA pol II. Apart from its role on myogenic gene expression, Cdk9 regulation of muscle‐specific microRNAs in the early stage of cardiomyogenesis is poorly understood. Here we demonstrate that Cdk9 not only regulates myogenic transcription factors, but also controls muscle‐specific microRNAs. During cardiac differentiation of mouse embryonic stem cells, high Cdk9 expression preceded up‐regulation of miR‐1. To investigate potential regulatory roles of Cdk9 on cardiac microRNAs and myogenesis genes, we overexpressed Cdk9 in myoblast C2C12 cells, which resulted in significant induction of miR‐1 and miR‐206, while miR‐133 was downregulated. Moreover, expression levels of MyoD and Srf, key regulators of myogenesis, also increased in cells with overexpression of Cdk9 . We further observed Cdk9 ‐mediated apoptosis in C2C12 cells corresponding to induction of miR‐1 expression levels. Thus, Cdk9 plays a complex role in myocyte progenitor differentiation and apoptosis by regulating myogenic protein and muscle‐specific microRNA expression. J. Cell. Biochem. 119: 547–554, 2018. © 2017 Wiley Periodicals, Inc. Abstract : To investigate potential regulatory roles of Cdk9 on cardiac microRNAs and myogenesis genes, we overexpressed Cdk9 in myoblast C2C12 cells, which resulted in significant induction of miR‐1 and miR‐206, while miR‐133 was downregulated. Moreover, expression levels of MyoD and Srf, key regulators of myogenesis, also increased in cells with overexpression of Cdk9. We further observed Cdk9‐mediated apoptosis in C2C12 cells corresponding to induction of miR‐1 expression levels. Thus, Cdk9 controls myocyte progenitor cell growth, differentiation, and apoptosis by modulating myogenic transcription factors and myomiRs in a complex regulatory network.